Evaluation of fungicides against stem rot of groundnut caused by Sclerotium rolfsii Sacc under in vitro condition: Evaluation of fungicides against stem rot of groundnut caused by Sclerotium rolfsii Sacc under in vitro condition - S VIJAYKUMAR; R D PRASAD; B RAJESWARI; K S V P CHANDRIKA (Journal of Oilseeds Research, 2023)
The efficacy of five test fungicides viz., carboxin 37.5 % + thiram 37.5 %, tebuconazole 25 % EC, mancozeb 75 %WP, penflufen 13.28 % w/w + trifloxystrobin 13.28 % w/w FS and chlorothalonil 75 % WP were tested under in vitro by poisoned food technique against S. rolfsii in groundnut. Among five fungicides, penflufen + trifloxystrobin fungicide were found highly effective at all the concentrations (250, 500, 750 and 1000 ppm) tested and inhibited 100.0 % mycelial growth of S. rolfsii in groundnut as compared to control.